Hong Kong in Transition
XX, 327 p.
Keywords: This book presents an overview of critical developments surrounding the handover of Hong Kong to Chinese rule. Well-known commentators from a variety of disciplines examine the issues and events in the years leading up to the transfer of sovereignty, and in the eighteen months that followed. Major dilemmas are addressed in the economic, political, legal, social and diplomatic life of the territory, which remain in many cases unresolved and pressing as Hong Kong enters the new century.